Miscellaneous for the essential improvement of civil enforcement civil procedings. Proposals and reminders regarding new technologies (Acta Judicial Journal, 2023)
This paper adresses to carry out an in-depth analysis of various aspects of civil enforcement that can be improved in order to achieve an increase in its effectiveness and efficiency, the role that new technologies can play in this matter being transcendental. To make It happen , the entire logical-argumental journey begins with the enhancement of execution as part of the essential core of the fundamental right to effective judicial protection and, subsequently, crucial elements are exposed to verify at what points it is appropriate to adopt technological improvements to the civil procedings of execution maintaining the current regulation. Precisely, the development of the study is produced by observing common practical problems not forgetting the idea that with the lack of adequate means it will not be possible to eliminate the structural defects of the Civil jurisdiction executive system, which is applicable, subsidiarly to the other jurisdictional orders in all that there is procedural and objective compatibility with a view to satisfying the subjective rights of the performers.
Keywords: Civil execution, new technologies, artificial intelligence, blockchain, procedural efficiency, executive titles, embargoes, urgency, material means.